Effectiveness of Augmented Reality-Based learning in Enhancing Vocabulary at SMP IT AL-IHYA - Alya, Cania Henfaridja; Saragih, Mandra (Journal of English Language and Education, 2025)
This study aims to examine the effectiveness of Augmented Reality (AR)-based learning media in enhancing English vocabulary mastery among eighth-grade students at SMP IT AL-IHYA. The research employed Classroom Action Research (CAR) following the Kurt Lewin model, conducted in two cycles. Data collection involved observations, interviews, pre-tests, post-tests, and documentation. The results showed a significant improvement in students' vocabulary mastery. The pre-cycle average score was 64.48 with only 24% of students reaching the minimum mastery level. After the implementation of AR-based learning in Cycle I, the average score increased to 70 with 40% of students achieving mastery. In Cycle II, the class average rose sharply to 87.4, with 100% of students achieving mastery. Observation of student activity also improved, from 52.38% in the pre-cycle to 90.47% in Cycle II. Based on the N-Gain Score of 0.645, the effectiveness of the intervention was categorized as moderate. These findings suggest that AR-based learning not only improves vocabulary mastery but also increases student engagement in the learning process.